Factors influencing hikers’ litter behavior in national park in China - Sun, Huazhen; Yang, Feifei; Guo, Weifeng (Frontiers in Forests and Global Change, 2024)
The implementation of the litter behavior initiative aims to mitigate the generation of litter by hikers within the hiking trails of China’s national park. The present study employed the extended norm activation model (NAM) to examine the determinants of hikers’ intention to engage in litter behavior within the context of Wuyishan national park. This analysis incorporated three supplementary explanatory variables, namely environmental knowledge, connectedness to nature, and pro-environmental behavior in everyday life. Additionally, three control variables were included, namely gender, age, and education. A survey was conducted by researchers at Wuyishan national park, with a sample size of 466 hikers. The data obtained from the survey was analyzed using the statistical technique known as structural equation modeling. The findings indicate that the NAM effectively captured hikers’ litter behavior in national parks. Factors such as hikers’ awareness of consequences, ascription of responsibility, personal norm, environmental knowledge, connectedness to nature, and pro-environmental behavior in everyday life were found to significantly influence hikers’ intention to engage in litter behavior. The influence of age on hikers’ intention was shown to be significant and positive, suggesting that older hikers exhibited a greater willingness to engage in litter behavior compared to younger hikers. In conclusion, the study provided practical recommendations for improving the management of hiker trash and promoting sustainable development inside national parks.